Fault Detection and Predictive Maintenance Paradigm for Solar PV Systems - Limpaporn, Poompat; Khomfoi, Surin (My University, 2024)
This research paper introduces the Box Plot model for the fault detection and degradation analysis in solar photovoltaic (PV) systems. The suggested method contains a mathematics equation and systematic flowchart algorithm to detect and categorize various fault types, such as direct current (DC) ground fault, DC overvoltage fault, and partial shading. The technique evaluates and monitors the performance and degradation of PV panel by processing comprehensive input data such as voltage, current, irradiance, temperature, power, solar PV systems related data and PV panel parameter data. The Box Plot model efficiently monitors fault analysis and degradation detection, adapting to various operational conditions with accuracy, resulting in a powerful tool for assessing the reliability and performance of solar PV systems. The Box Plot model is tested by using the three sets of the solar PV power plant collected data from the PV panel strings in the same array that nearby each other and verifying the Box Plot model effectiveness by comparing the model analysis result with the solar PV power plant operation and maintenance report. This methodology makes a major contribution to predictive maintenance operations and ensuring more reliability for the PV systems.
Keywords: Box Plot model; degradation; fault detection; PV panel; solar PV systems